2018
DOI: 10.1021/acs.langmuir.7b04053
|View full text |Cite
|
Sign up to set email alerts
|

SnO2 Inverse Opal Composite Film with Low-Angle-Dependent Structural Color and Enhanced Mechanical Strength

Abstract: Structural colors are attracting considerable attention for their advantages of environmental friendliness and resistance to fading. However, the weak mechanical strength and intrinsic iridescent color restrict their widespread application. This article describes a SnO inverse opal composite film with low-angle-dependent structural color and enhanced mechanical strength. In the present study, a direct template method was used to prepare SnO inverse opals, which were then embedded in polydimethylsiloxane (PDMS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…PS and PS@SiO 2 microspheres suspensions were synthesized as previously reported in Liu, et al. [ 25 ] and Wu et al. [ 26 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PS and PS@SiO 2 microspheres suspensions were synthesized as previously reported in Liu, et al. [ 25 ] and Wu et al. [ 26 ]…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of PS and PS@SiO 2 Microspheres: PS and PS@SiO 2 microspheres suspensions were synthesized as previously reported in Liu, et al [25] and Wu et al [26] Synthesis of Vitrimer Elastomers: First, HTPB, PTMG, and GLY were dried in a 120 °C vacuum oven for 4 h, then, HTPB, PTMG, GLY, and IPDI (Table S1, Supporting Information, shows the specific mass) were added into bottles at 60 °C. Thereafter, 1% DBTDL was sequentially added and vortexed.…”
Section: Methodsmentioning
confidence: 99%
“…[ 37–39 ] With the increase of detector angle from 10° to 60°, the wavelength changed little and showed the low angle dependence. In our previous study, [ 40 ] the diffuse reflectance spectra of SnO 2 inverse opal showed low angle dependence. The filling of PEG greatly improved the effective refractive index of TRPC, where the refractive index of PEG was 1.46 and that of air was only 1.…”
Section: Resultsmentioning
confidence: 93%
“…The sol-gel method is the most common preparation method for the 3D TMOPCs. [53][54][55][56][57][58] The compounds containing high-chemical active components are used as precursor mixed in the liquid phase. Then, a stable transparent sol system is formed by hydrolysis and condensation chemical reactions in the solution.…”
Section: Sol-gel Methodsmentioning
confidence: 99%